Synthesis of rare earth based nanomaterials - Ong, Ling Hui. (2011)
Discovered just a few years ago, graphene and graphene oxide has received great interest in the scientific community. Graphene oxide, being able to load and deliver drugs opens up possibilities for simultaneous bio-imaging and therapy. Meanwhile, in the near-infrared region, biological samples have low background fluorescence signals, providing high signal to noise ratio. Also, near-infrared radiation can penetrate into sample matrices deeply due to low light scattering. However, there lies the problem of low light scattering and photobleaching Solution came in the form of semiconductor nanocrystals, or quantum dots. Though brighter fluorescence was achieved and them being more resistant to degradation by light, tracking is made difficult due to “blinking” from collective fluorescence. NaYF4: Yb, Er nanocrystals, also quantum dots, were subsequently discovered to solve the problem of “blinking” by traditional quantum dots. NaYF4: Yb, Er nanocrystals are excited by infrared light with each of the quantum dots absorbing and emit fluorescence independently not collectively. Hence, this project aims to incorporate NaYF4: Yb, Er nanocrystals on graphene oxide in hope of combining the properties of both, and also the possibility of improving the aqueous solubility of the nanocrystals. Experiments conducted were able to attach NaYF4: Yb, Er nanocrystals to the graphene surfaces rich in hydroxyl groups giving them high hydrophilicity. Further experiments also suggest a faster and improved way to obtain NaYF4: Yb, ER on expholiated oxidized graphene through solvothermal synthesis. This is opposed to the commonly used hydrothermal synthesis (Modified Hummer’s Method).